Influence of Valve Core Structure on Flow Rate and Internal Flow Field of Pressure Independent Control Valve. Issue 1 (July 2020) - Fan, Y L; Wang, J; Huang, J; Peng, L; Li, Z
Abstract: To study the influence of valve core structure on pressure independent control valve, based on the computational fluid dynamics method, the 3D model of pressure independent control valve under different control valve core structure is established. Then the influence of different control core structure on valve flow rate under different pressure was studied, the pressure and velocity distribution of the internal flow field are obtained. The results show that, under the same flow characteristics, a maximum flow capacity under different valve core difference of 20%, the pressure and velocity distribution of the internal flow field is different. Reasonable choice of different valve core structures for different working conditions can improve the stability of the flow field in the valve.